Stop eulogizing, complicating or straitjacketing the concept of organizational unlearning, please. Issue 2 (6th February 2017) - Tsang, Eric W.K.
Abstract : Purpose: This paper aims to provide some comments on the four papers, other than the author's own, that were included in a recent special issue on organizational unlearning. Design/methodology/approach: The author carefully reads these papers and identify problems that may hinder unlearning research. Findings: While each paper has its own merits, a common problem shared by the papers is that the concept of organizational unlearning is unnecessarily eulogized, complicated or straitjacketed. Research limitations/implications: The author's discussion focuses only on a problem related directly to the concept of unlearning, and does not cover other, though less serious, issues. Originality/value: The author's comments help readers better understand the concept of unlearning and so facilitate the further development of unlearning research.